A Framework for Optimizing Work–Life Balance Practices in Australia: Perceived Options for Employee Support. Issue 3 (September 2016) - Jenkins, Stacey; Bhanugopan, Ramudu; Lockhart, Pamela
Abstract : Drawing from institutional theory, this study explored work–life balance (WLB) practices in Australian small and medium enterprises. Data were obtained from a sample of 219 managers. The authors identified organizational characteristics associated with the adoption of 4 groups of WLB practices using a causal model. Of the 3 models tested, the final model supported a conceptual framework that included 4 domains: flexible work options, leave programs, support benefits, and care arrangements. The findings suggested that organizational characteristics—namely, industry type and location—affected WLB practices. Implications for theory and practice are discussed along with avenues for future research.